Consumer Preference Influence Towards Revenue Optimization for Local Brand Accessories in Bandung - Raden Aswin Rahadi; Shanaya Ratu Shafira (Jurnal Manajemen Indonesia, 2020)
Planning a careful market and good product strategy in launching new products is very important to help new company succeed in the market with knowing the consumer preference and cashflow projection. This research raises the issue of the importance of consumer preference to get optimal revenue on launching new product. This research was conducted at Soigne, a local brand accessory in Bandung. The purpose of this study is to determine how the company conducts feasibility study through consumer preferences for knowing the suitable price and products to launch in 2019. This study also analyses the sensitivity analysis to delimit the changes of financial conditions. According to the result of the research, there are recommendations that can be applied in Soigne to launch a suitable product to gain optimal revenue based on consumer preference. The best combination product to launch in Soigne is accessories product between earrings, bracelet, and necklace with neutral color, simple design, and price range between IDR 100,000.00 to IDR 250,000.00. Customer service, packaging design, materials and durability is other factor that important to provide by the company. For the optimal revenue, Soigne recommended to launch earrings with price IDR 149,000.00, bracelet with price IDR 169,000.00, and necklace with price IDR 189,000.00 in the next one year and increase 10% for the price in the next two and three years which are the best financial scenario of researcher projection. Keywords— Cashflow Projection; Consumer Preference; Feasibility Study; Launching New Product; and Sensitivity Analysis